HUBUNGAN SPIRITUALITAS DENGAN KUALITAS HIDUP LANSIA DI DESA PONTOLO KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Firmawati Firmawati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Spirituality further increased in older people because the elderly have more time for religious activities and seek to understand the religion. Spirituality is one of the parameters that affect quality of life. This study aims to determine the relationship of spirituality to the the quality of life of the elderly in the village Pontolo. The correlation descriptive study design, sample size of 69 people with a total sampling methods, research instruments such as questionnaires and analysis of test data using Spearmen Rank (Rho). The results showed respondents with spirituality being the 36 respondents (52.2%), high spirituality as much as 33 respondents (47.8%), quality of life pretty as much as 30 respondents (43.5%), and a good quality of life for as many as 39 respondents (56.5%), ρ-value=0.000 with a correlation coefficient showing results=0.606 (Positive) which indicates a strong and direct relationship between the two variables. The Conclusion in this research is relationship between spirituality with elderlylife quality in the village Pontolo, Sub-district of Kwandang, North Gorontalo.